High hardness and fatigue resistance of CoCrFeMnNi high entropy alloy films with ultrahigh-density nanotwins. (August 2020) - Wang, Ze; Wang, Cheng; Zhao, Yi-Lu; Hsu, Ya-Chu; Li, Chia-Lin; Kai, Ji-Jung; Liu, Chain-Tsuan; Hsueh, Chun-Hway
Abstract: Development of film materials has been limited by the hardness-fatigue resistance trade-off. The purpose of the present study was to obtain films with a combination of both high hardness and strong fatigue resistance. To achieve this, CoCrFeMnNi high entropy alloy films (HEAFs) were fabricated with three different structures: amorphous, high-density nanotwinned crystal structure with twin spacings of 2.2–5.6 nm, and ultrahigh-density nanotwinned columnar grains with twin spacings of 1.2–2.5 nm. Nanoindentation with dynamic mechanical analysis was used to measure the hardness and perform the fatigue tests. While higher twin densities could dissipate more energy by detwinning during fatigue loading to enhance the fatigue resistance, twin spacings larger than and small than 2 nm could, respectively, result in hardening and softening. Our results showed a high hardness of 9 GPa and fair fatigue resistance ( 10 4 cycles) for both amorphous and high-density nanotwinned crystalline layers. For the ultrahigh-density nanotwinned columnar grain structure, a high hardness of 8.5 GPa and an excellent fatigue resistance ( 10 6 cycles) were obtained. The outstanding fatigue resistance and high hardness were attributed to the synergistic effect of strain hardening and detwinning of ultrahigh-density nanotwins. The results not only enable CoCrFeMnNi HEAFs with a predominant combination of hardness and fatigue resistance, but also shed light on a new perspective for overcoming the conflict between hardness and fatigue resistance in film materials for microelectromechanical applications. Highlights: We fabricated high entropy alloy films with different structures containing nanotwins. We used dynamic mechanical analyses to measure hardness and perform fatigue tests. Nanotwins dissipate energy by detwinning under loading to enhance fatigue resistance. Twin spacings larger and small than 2 nm could, respectively, yield hardening and softening. Films with twin spacings spanning across 2 nm showed excellent hardness-fatigue resistance.